2013
DOI: 10.3109/03008207.2013.847096
|View full text |Cite
|
Sign up to set email alerts
|

Distributions of types I, II and III collagen by region in the human supraspinatus tendon

Abstract: The mechanical properties of the human supraspinatus tendon (SST) are highly heterogeneous and may reflect an important adaptive response to its complex, multiaxial loading environment. However, these functional properties are associated with a location-dependent structure and composition that have not been fully elucidated. Therefore, the objective of this study was to determine the concentrations of types I, II and III collagen in 6 distinct regions of the SST and compare changes in collagen concentration ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 25 publications
2
65
0
Order By: Relevance
“…[1][2][3][4] As a result, specific locations of the human SST exhibit significantly different fiber alignment and tensile modulus during tensile loading, 5,6 as well as compositional differences (i.e., collagens, proteoglycans) by location. 3,7 Similarly, the bovine deep digital flexor tendon (DDFT) functions in a multiaxial physiological loading environment with forces that vary at different anatomical locations: the proximal region is mostly loaded in tension, while the distal region is also compressed against the navicular bone during normal joint function. [8][9][10][11][12][13] Our previous study, 14 which evaluated the DDFT as an easily accessible example of a complexly loaded tendon with tissue-level properties that vary by location, 8 demonstrated that the proximal and distal regions exhibited different elastic mechanical properties, yet similar viscoelastic properties, and inhomogeneous proteoglycan distribution and collagen organization.…”
mentioning
confidence: 99%
“…[1][2][3][4] As a result, specific locations of the human SST exhibit significantly different fiber alignment and tensile modulus during tensile loading, 5,6 as well as compositional differences (i.e., collagens, proteoglycans) by location. 3,7 Similarly, the bovine deep digital flexor tendon (DDFT) functions in a multiaxial physiological loading environment with forces that vary at different anatomical locations: the proximal region is mostly loaded in tension, while the distal region is also compressed against the navicular bone during normal joint function. [8][9][10][11][12][13] Our previous study, 14 which evaluated the DDFT as an easily accessible example of a complexly loaded tendon with tissue-level properties that vary by location, 8 demonstrated that the proximal and distal regions exhibited different elastic mechanical properties, yet similar viscoelastic properties, and inhomogeneous proteoglycan distribution and collagen organization.…”
mentioning
confidence: 99%
“…35,36) An injured ligament may become physically weaker and stiffer during the healing process as rigidity increases and elasticity decreases. 37) The group treated with Laennec maintained physical characteristics that were similar to those of the normal ligament group at 1 and 4 weeks after treatment. Since our biomechanical test results show no significant differences in physical characteristics between normal and saline treatment group, more supporting experiments may be necessary.…”
Section: Discussionmentioning
confidence: 69%
“…), lubricin, tenascin‐C, and collagen oligomeric matrix protein (COMP), which may contribute mechanically (Fig. ) . Interestingly, previous studies showed that fibrils formed by collagen types II and III, related with tendon healing, were smaller than these of collagen type I .…”
Section: Contribution Of Specific Constituents To Mechanicsmentioning
confidence: 99%
“…Interestingly, previous studies showed that fibrils formed by collagen types II and III, related with tendon healing, were smaller than these of collagen type I . Collagen type II content was higher near the insertion of human SST, which experiences more compressive loading compared to the midsubstance, and collagen type III content was inversely correlated with tendon tensile modulus and collagen alignment . Mutations of collagen type V causes joint hypermobility in classic Ehlers‐Danols syndrome, which motivates the evaluation of the contribution of collagen type V to tendon mechanics .…”
Section: Contribution Of Specific Constituents To Mechanicsmentioning
confidence: 99%